THE AUR 2025: UMPSA recognised as 163rd best in Asia, ranked 9th among universities in Malaysia - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 23 April 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has achieved a proud milestone by being ranked 163rd best in Asia according to the Times Higher Education Asia University Rankings 2025 (THE AUR 2025) while also maintaining its position as the top university within the Malaysian Technical University Network (MTUN).